11beta-Hydroxysteroid Dehydrogenase Type 1 Regulation by Intracellular Glucose 6-Phosphate Provides Evidence for a Novel Link between Glucose Metabolism and Hypothalamo-Pituitary-Adrenal Axis Function. - Walker, E; Ahmed, A; Lavery, G; Tomlinson, J; Kim, S; Cooper, MS; Ride, J; Hughes, B; Shackleton, C; McKiernan, P; Elias, E; Chou, J; et al. (2007)
Microsomal glucose-6-phosphatase-alpha (G6Pase-alpha) and glucose 6-phosphate transporter (G6PT) work together to increase blood glucose concentrations by performing the terminal step in both glycogenolysis and gluconeogenesis. Deficiency of the G6PT in liver gives rise to glycogen storage disease type 1b (GSD1b), whereas deficiency of G6Pase-alpha leads to GSD1a. G6Pase-alpha shares its substrate (glucose 6-phosphate; G6P) with hexose-6-phosphate-dehydrogenase (H6PDH), a microsomal enzyme that regenerates NADPH within the endoplasmic reticulum lumen, thereby conferring reductase activity upon 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1). 11beta-HSD1 interconverts hormonally active C11beta-hydroxy steroids (cortisol in humans and corticosterone in rodents) to inactive C11-oxo steroids (cortisone and 11-dehydrocorticosterone, respectively). In vivo reductase activity predominates, generating active glucocorticoid. We hypothesized that substrate (G6P) availability to H6PDH in patients with GSD1b and GSD1a will decrease or increase 11beta-HSD1 reductase activity, respectively. We investigated 11beta-HSD1 activity in GSD1b and GSD1a mice and in two patients with GSD1b and five patients diagnosed with GSD1a. We confirmed our hypothesis by assessing 11beta-HSD1 in vivo and in vitro, revealing a significant decrease in reductase activity in GSD1b animals and patients, whereas GSD1a patients showed a marked increase in activity. The cellular trafficking of G6P therefore directly regulates 11beta-HSD1 reductase activity and provides a novel link between glucose metabolism and function of the hypothalamo-pituitary-adrenal axis.